Using power to achieve network outcomes: why Funders should maintain a hands-on approach. (1st October 2016) - Bashir, Mohsin
Abstract: This article analyses the effects of organizational power on the outcomes of two public service networks in rural Pakistan. It finds that even networks that are alike when compared along the determinants of network effectiveness, as identified in the seminal work done by Turrini et al., can have considerably different outcomes. It also finds that the outcomes of these networks can be significantly altered by the exercise of power, or lack thereof, by influential collaborators. Based on these findings, the article concludes that funders in a public service network should adopt a hands-on approach to ensure that the network achieves its stated goals.